Legal Awareness Among KNPI Youth in Indramayu District, Indramayu Regency - Dimas Hilmawan Kurnia; Ahmad Suhendra (International Research and Development for Human Beings (IRDH), 2025)
Legal awareness is an essential aspect in building an orderly and just society, particularly among youth who serve as agents of change. This study aims to analyze the level of legal awareness among KNPI youth in Lemah Abang District, Indramayu Regency, identify supporting and inhibiting factors, and formulate effective strategies for strengthening legal awareness. The research employed a descriptive qualitative method with a participatory approach, using seminars, legal counseling, group discussions, case-based training, and moot court simulations. Data were collected through observation, interviews, documentation, and pre-test and post-test assessments of 45 participants. The findings reveal that the average level of legal understanding increased from 58% before the program to 84% afterward, with significant improvements in knowledge, comprehension, attitudes, and legal behavior. Supporting factors included active youth participation and community leader involvement, while constraints were related to limited time, diverse educational backgrounds, and social environmental influences. These results highlight the importance of youth organization–based legal education as a sustainable strategy for fostering a law-abiding young generation